An analysis of the "reflexive modernization" and the "risk society": The risk of the application of "artificial intelligence" in the drafts of brazilian judicial decisions - Pimentel , Alexandre Freire; Araújo , Bruno Manoel Viana de; Martins , Michelle Fernanda; Maciel, Thiago Mota (Seven Editora, 2023)
This scientific article seeks to analyze the risks of the application of artificial intelligence in the drafts of Brazilian judicial decisions in the context of reflexive modernization and risk society. Through the deductive method and an exploratory research, the concepts of reflexive modernization and risk society were analyzed. The concept of artificial intelligence and its applications were also explored. Finally, the risks of the application of artificial intelligence in the drafts of Brazilian judicial decisions were studied, as well as an overview of artificial intelligence projects in this sense in Brazilian courts. The methodology adopted was the literature review, through legislation, scientific articles, doctrine and specialized journals. In the end, it was concluded that it is essential to respect the ethics, governance and transparency guidelines established by Resolution 332 of the National Council of Justice. It was also concluded that, for the effectiveness of transparency, it is essential that the codes of the algorithms are open source and available to any and all citizens, as well as that the application of artificial intelligence occurs through supervised learning. DOI:https://doi.org/10.56238/sevened2023.006-045